PEMBERDAYAAN KADER TENTANG PERAWATAN PAYUDARA - Najahah, Imtihanatun; Marliana, Yunita; Saudia, Baiq Eka Putri (Poltekkes Kemenkes Mataram, 2025)
Exclusive breastfeeding is a form of maternal behavior in providing exclusive breast milk to her baby. In Indonesia, the achievement rate of exclusive breastfeeding reached 37.3% in 2018. Meanwhile, in West Nusa Tenggara Province, the coverage of exclusive breastfeeding in 2018 was at the lowest figure, namely 20.3%. The achievement of exclusive breastfeeding in Batu Layar District was 98.8% and for exclusive breastfeeding coverage in Lembah Sari Village was 97.4%, this figure is lower than the District figure. One of the causes of this failure in breastfeeding is because the mother does not feel comfortable when the first week of the baby's birth is because in the first week the production of breast milk has started to increase but is not followed by the maximum sucking power of the baby so that the mother tends to experience breast milk stasis.The aim of this Community Service activity is to empower Community health workers by increasing their knowledge and skills in breast milk pumping techniques.Through integrated health Community health workers, pregnant and postpartum women can obtain information related to breast care (expressing breast milk). Efforts that can be made to overcome the current challenges of exclusive breastfeeding coverage include empowering cadres through breast care (expressing breast milk) classes consisting of 30 Community health workers. Community service activities are carried out by providing education and demonstrations of breast care (expressing breast milk) through video media uploaded to YouTube. The results of the community service show a change in skills, from the majority having adequate skills to becoming skilled. In conclusion, empowering Community health workers through breast care classes is effective in improving breast milk expression skills, making Community health workers agents of change who are ready to support the success of exclusive breastfeeding in Lembah Sari Village.